Organotin (IV) complexes of 2-hydroxyacetophenone-N (4)-cyclohexylthiosemicarbazone (H 2 dact): Synthesis, spectral characterization, crystal structure and biological studies - M.A., Affan; M.A., Salam; Fasihuddin B., Ahmad; White,, Fraser; Hapipah M., Ali (Elsevier, 2012)
Four new organotin(IV) complexes of the type [MeSnCl(dact)] (2), [BuSnCl(dact)] (3), [PhSnCl(dact)] (4) and [Ph2Sn(dact)] (5) were synthesized by the direct reaction of 2-hydroxyacetophenone-N(4)- cyclohexylthiosemicarbazone [H2dact, (1)] and organotin(IV) chloride(s) in absolute methanol. The ligand [H2dact, (1)] and its organotin(IV) complexes (2–5) have been characterized by CHN analyses, molar conductivity, UV–Vis, FT-IR, 1 H, 13C and 119Sn NMR spectral studies. The molecular structure of complex (5) has also been determined by single-crystal X-ray diffraction. The crystal structure of complex (5) showed that the ligand is doubly deprotonated at the oxygen and sulfur atoms and is coordinated to the tin(IV) atom through thiolate-S, azomethine-N and phenoxide-O atoms. X-ray diffraction studies indicated that complex (5) is a monomer and the central tin(IV) atom is five coordinated in a distorted trigonal bipyramidal geometry. The cytotoxicity of the ligand (1) as well as its organotin(IV) complexes (2–5) was studied against Artemia salina. The in vitro antibacterial activities of these compounds were also evaluated. The screening results have shown that the organotin(IV) complexes (2–5) have better antibacterial activity than the free ligand. Furthermore, it has been shown that diphenyltin(IV) derivative (5) exhibits significantly better activity than the monoorganotin(IV) derivatives (2–4).